The Effect of Perceptions of The Mathematics Social Values on The Attitude of Respecting Mathematics - Yayan Eryk Setiawan; Surahmat Surahmat; Sunismi Sunismi; Zainal Abidin; Sunardi Sunardi (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the effect perceptions of the mathematics social value on the attitude of respecting mathematics. This type of research is quantitative research. The sample of this research was 65 students in one semester of the mathematics education study program at the Islamic University of Malang. The data collected in this research is the result of a questionnaire on the perception of mathematics social values and attitude of respecting mathematics. The questionnaire in this study consisted of five statements about mathematics social values and four statements about the attitude of respecting mathematics. The results of the questionnaire were analyzed by correlation test and regression test with SPSS. The results showed that there was a correlation between perceptions of mathematics social values and attitude toward respecting mathematics. The results also show that the perception of mathematics social value has a positive effect on student attitude of respecting mathematics in learning mathematics by 55.2%. This influence is generally due to positive perceptions of the social values of mathematics. Thus learning is expected to instill social values of mathematics so that the attitude of respecting mathematics increases and ultimately increases student achievement in mathematics.